2018
DOI: 10.1073/pnas.1812125115
|View full text |Cite
|
Sign up to set email alerts
|

RPA1 binding to NRF2 switches ARE-dependent transcriptional activation to ARE-NRE–dependent repression

Abstract: NRF2 regulates cellular redox homeostasis, metabolic balance, and proteostasis by forming a dimer with small musculoaponeurotic fibrosarcoma proteins (sMAFs) and binding to antioxidant response elements (AREs) to activate target gene transcription. In contrast, NRF2-ARE–dependent transcriptional repression is unreported. Here, we describe NRF2-mediated gene repression via a specific seven-nucleotide sequence flanking the ARE, which we term the NRF2-replication protein A1 (RPA1) element (NRE). Mechanistically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 50 publications
3
50
0
Order By: Relevance
“…Additionally, the total protein concentration and the levels of IL-6 and TNF-α in each sample were detected with the Pierce BCA Protein Assay Kit (Thermo Fisher Scientific), IL-6 ELISA Kit ELISA kit (Invitrogen) and TNF-α ELISA Kit (Invitrogen) according to the manufacturer's instructions. Lung tissues in different groups were collected for qPCR and western blot detection, and part of lung tissues was fixed using 10% buffered formalin, then the tissues were embedded in paraffin for histological analyses as the references [25,[30][31][32]. Herein, a scoring system of 0-4 was used for the evaluation of lung injury as the reference [33].…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Additionally, the total protein concentration and the levels of IL-6 and TNF-α in each sample were detected with the Pierce BCA Protein Assay Kit (Thermo Fisher Scientific), IL-6 ELISA Kit ELISA kit (Invitrogen) and TNF-α ELISA Kit (Invitrogen) according to the manufacturer's instructions. Lung tissues in different groups were collected for qPCR and western blot detection, and part of lung tissues was fixed using 10% buffered formalin, then the tissues were embedded in paraffin for histological analyses as the references [25,[30][31][32]. Herein, a scoring system of 0-4 was used for the evaluation of lung injury as the reference [33].…”
Section: Animal Experimentsmentioning
confidence: 99%
“…In this model, RPA1 becomes a novel NRF2-binding partner which competes with sMAF for NRF2 binding. The in silico and RNAseq data sets indicates that the NRF2-RPA1-ARE complex may also transcriptionally inhibit other genes, including cancer related gene, FOCAD [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ahrr and tiparp are an integral part of AHR signaling and both have been shown to negatively regulate AHR activity by distinct mechanisms (MacPherson et al 2014). In addition, recent studies demonstrated that nrf2b, a homolog of mammalian nuclear factor, erythroid 2-like 2 (NFE2L2) also act as a repressor of gene expression (Bahn et al 2019;Liu et al 2018;Thangasamy et al 2011;Timme-Laragy et al 2012). The expression of these transcripts was upregulated in response to PCB126 exposure.…”
Section: Discussionmentioning
confidence: 99%